2019
DOI: 10.1111/jvim.15482
|View full text |Cite
|
Sign up to set email alerts
|

Randomized field trial on the effects of body weight and short transport on stress and immune variables in 2‐ to 4‐week‐old dairy calves

Abstract: Background Whether underweight calves respond differently to transport stress, enhancing their disease risk, is currently unknown. Objective To determine the effects of low body weight and transport stress on immune variables. Animals Twenty‐one 2‐ to 4‐week‐old male Holstein calves, housed on a commercial farm. Methods Randomized clinical trial. Full factorial design with 4 treatment groups: low body weight (≤46 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 60 publications
(183 reference statements)
2
24
0
Order By: Relevance
“…This difference might reflect the activation of the immune system to redistribute more T cells from the secondary lymphoid organ into the peripheral blood. Masmeijer et al [ 49 ] indicated that, in young calves between 14 and 28 days of age, transport-related higher glucocorticoids may cause a robust leukocyte redistribution by inducing increased expression of surface receptors (e.g. CD172a, CD11a) on stress-activated monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference might reflect the activation of the immune system to redistribute more T cells from the secondary lymphoid organ into the peripheral blood. Masmeijer et al [ 49 ] indicated that, in young calves between 14 and 28 days of age, transport-related higher glucocorticoids may cause a robust leukocyte redistribution by inducing increased expression of surface receptors (e.g. CD172a, CD11a) on stress-activated monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Transport stress might also lead to other shifts in immune cell subsets, including an increase in monocytes, eosinophils and basophils [ 27 , 54 ]. In fact, transport of young calves (14 until 28 days of age) is associated with an increased production in glucocorticoids, which can cause a robust leukocyte redistribution [ 49 ]. This general mechanism of redistribution may also explain the current effects of the conditioned truck on total WBC and some of the related cells.…”
Section: Discussionmentioning
confidence: 99%
“…24 Stressed cattle can have increased levels of inflammatory cytokines, acute phase proteins, and neutrophils. [25][26][27][28][29][30] In cattle, dexamethasone and corticotrophin-releasing hormone trigger acute phase responses that amplify the response to inflammatory stimuli 28,31 and reduce neutrophil clearance. 32 Similarly, viruses stimulate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is somewhat surprising that HS results were so low, especially following transportation. Transportation is a major cause of stress in calves ( 32 34 ), and has been associated with increased prevalence of diseases, especially respiratory diseases ( 14 , 15 ). However, the differences from our results to previous reports are likely explained by the fact that calves in our study received adequate amounts of good quality colostrum, were housed individually, and were transported at a very young age.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Van Engen and Coetzee ( 14 ) described the intricate role of transportation on immune suppression and increased inflammation, pre-disposing feedlot cattle to pneumonia. Transportation increases disease susceptibility of calves ( 15 ) and performing preventive interventions before transportation is associated with enhanced health and performance after transportation ( 16 ). However, vaccinations and metaphylaxis are often performed after transportation ( 17 ).…”
Section: Introductionmentioning
confidence: 99%